IMPLEMENTASI PENDIDIKAN INKLUSIF MULTIKULTURAL UNTUK MEMBENTUK KARAKTER SISWA YANG TOLERAN: KASUS DI KELAS VI MIN 2 GUNUNGKIDUL - Ika Damayanti; Frisma Mufti Hafisyah Dewanti; Happy Asy-Syifaini Abaddiyah; Sri Antari; Andi Prastowo (PGSD UNIKA SANTU PAULUS RUTENG, 2021)
Abstract : Madrasas are general educational institutions characterized by Islam. In addition to having a goal to form intelligent students, Madrasas also have a humanitarian mission. Inclusive Education in Madrasas exists as a form of instilling humanist and religious characters. The purpose of this study is to describe the implementation of multicultural inclusive Islamic education in forming religious humanist students in Class VI MIN 2 Gunungkidul. The method used in this research is a case study with the results of the study showing that (1) MIN 2 Gunungkidul has been an inclusive school since 2015 and in implementing inclusive education in class VI the learning process is carried out by not separating inclusive students from general students by means of teachers interacting with each other. collaborate in helping inclusive students learn (2)Before the Covid-19 inclusive learning was held in the classroom and after the Covid-19 the school had a home visit program that aims for teachers to help inclusive students learn (3) The implementation of religious humanism in Class VI is seen with There are several programs carried out by schools that aim to foster a tolerant character, namely reciting and reading Asmaul Husna, performing Duha prayers, holding activities on Islamic holidays, getting used to 5S, and doing social services to the surrounding community. Keywords: Implementation, Inclusive Islamic Education, Multicultural, Tolerant, Religious Humanist.